A Simple Evaluation Method of Seismic Resistance of Residential House under Two Consecutive Severe Ground Motions with Intensity 7 - Kojima, Kotaro; Takewaki, Izuru (Frontiers in Built Environment, 2016)
In the 2016 Kumamoto earthquake in Japan, two severe ground shakings with the seismic intensity 7 (the highest level in Japan Metheorological Agency (JMA) scale; approximately X-XII in Mercalli scale) occurred consecutively on April 14 and April 16. In the seismic regulations of most countries, it is usually prescribed that such severe earthquake ground motion occurs once in the working period of buildings. In this paper, a simple evaluation method is presented on the seismic resistance of residential houses under two consecutive severe ground motions with intensity 7. Therefore the proposed method can be used for the design of buildings under two consecutive severe ground motions. The present paper adopts an impulse as a representative of near-fault ground motion and two separated impulses are used as the repetition of intensive ground shakings with the seismic intensity 7. Two scenarios to building collapse (collapse limit in terms of zero restoring force with P-delta effect and collapse limit in terms of maximum deformation) under two repeated severe ground shakings are provided and energy consideration is devised for the response evaluation. The validity and accuracy of the proposed theories are discussed through numerical analysis using recorded ground motions.